The Impact of Superior Canal Dehiscence on Power Absorbance, Otoacoustic Emissions, and Hearing in Fat Sand Rats. Issue 7 (August 2021) - Attias, Joseph; Rabinovics, Naomi; Nageris, Benny; Hilly, Ohad
Abstract : Background: Superior Semicircular Canal Dehiscence (SSCD) may lead to vestibular and auditory impairments. Objective: To study the effects of power absorbance (PA), Distortion Product Otoacoustic emissions (DPOAE), and hearing thresholds in normal ears of fat sand rats, after a bullotomy, creation and patching. Methods: SSCD was performed unilaterally in eight normal hearing animals while the contra-lateral un-operated ear was used as a control. Measures included auditory brain stem responses thresholds for air and bone conduction stimuli, DPOAEs and PA at peak pressure. Results: The normal PA pattern of the animals grossly resembled that of human ears. A bullotomy generated specific, large and significant ( p  < 0.0001) changes in PA without altering hearing thresholds. SSCD significantly decreased PA at low ( p  < 0.02) and increased at high frequencies ( p  < 0.03), but on a smaller scale than the bullotomy. SSCD, induced a mean air-bone gaps of 24.3 for clicks, and 31.2 dB for 1 kHz TB. SSCD also increased the DPOAEs levels by mean of 10.1 dB SPL ( p  < 0.03). Patching the dehiscence, reversed partially the PA changes, the auditory threshold shifts, and the DPOAEs levels to pre-SSCD values. Conclusions: SSCD affects both incoming and emitting sounds from the ear, probably due to its effect on cochlear impedance and stiffness of the middle and inner ear. The presence of DPOAEs and ABGs indicated a "third window" disease, i.e., SSCD. Due to similar PA patterns after bullotomy and SCCD, PA alone has limited diagnostic yield for patients with SCCD.